Investigating the Interaction of Nanodiamonds with Human Serum Albumin and Induced Cytotoxicity - Chen, Miaomiao; Zuo, Xiaoshuang; Xu, Qinqin; Wang, Rong; Fan, Suhua; Wu, Hai (Journal of Spectroscopy, 2019)
Nanodiamonds (NDs) have been recognized as emerging carbon-based delivery vehicles due to their biocompatibility. NDs were reported to be nontoxic and suited for biomedical applications in the complete cell culture medium. However, in this study, the cytotoxicity of NDs in serum-free medium was studied and indicated that serum proteins in cell culture medium played significant effect on the toxicity of NDs. Therefore, the interaction mechanism between NDs and a serum protein (human serum albumin, HSA) was first investigated by fluorescence quenching technique and circular dichroism (CD) spectrometry. The results suggest that HSA strongly bonds on the NDs surface to form “protein corona,” which not only prevents the aggregation of NDs and improves its stability but also inhibits the cytotoxicity of NDs. In serum-free medium, NDs exhibited obvious toxicity toward the human lung epithelial cell line (BEAS-2B) and showed concentration-dependent cytotoxicity. In the presence of bovine serum albumin (BSA), which shares structural homology and similar properties with HSA, toxicity of NDs was apparently inhibited. Therefore, the interaction between serum protein and NDs should be considered in the understanding of the biological effects of NDs exposure in biomedical applications.